The educational process in the implementation and development of the “EspiAí” project: report of an experience (Research, Society and Development, 2022)
This experience report deals with the implementation and development of a pedagogical project called “EspiAí”, implemented in a state school of Technical High School in the state of Pará. In the initial phase, the referred project directly involved 11 students and 4 teachers of the school. The objective of the work was to educate for the cultural development of making technology in the school environment. For this, classes were held in accordance with the FIC Desenvolvimento Mobile course, which was offered to the school community at that time. In fact, the following problem emerged: How to develop an application (mobile application) that could bring logistical, administrative and didactic-pedagogical information to the school and extra-school communities? From this question, the idea of ​​building the “EspiAí” mobile application was born, which, consequently, motivated the elaboration of the project of the same name and enabled virtual access in an interactive and practical way to all sectors of the school. In the path followed, any doubts about the use of mobile technologies were clarified, as well as the use of various technological resources for the construction of applications. The project experience allowed us to better understand the students' aspirations and, in this way, plan clearer and more meaningful guidelines for them.